Microbial quality indicators and physicochemical properties of a Portuguese traditional dry-fermented sausage along processing - Cadavez, Vasco (2018)
Linguica is a traditional Portuguese dry1ermented sausage whereby chopped pork is macerated with water, wine, salt, garlic and pepper, and undergoes processes of maturation, smoking and drying. While they are highly appreciated, their production is subject to extensive process variability and quality. The objective of this study was to investigate the interrelationship between quality indicator microorganisms such as total viable counts (TVC), Enterobacteriaceae and S. aureus and the physicochemical characteristics of the batter/sausage along processing of Linguica. Microbiological surveys following a batch throughout production were completed for three batches in each of the two factories under study. In every batch, samples of raw meat (n=3), batter before maceration (n=3), batter after 3- or 4-day maceration (n=3) and sausages after curing/drying (n=S) were extracted. Counts of TVC, Enterobacteriaceae, S. aureus as well as pH and water activity (Aw) were determined in duplicate for each sample. A principal component analysis (PCA) of these variables was carried out using the R software 2.14.2. The two-component PCA solution explained 73% of the total variability. The fact that, within the first principal component (46%), S. aureus and TVC had both positive correlation coefficients while pH and Aw had both negative correlations, indicated that along processing (i.e., decrease in pH and Aw), there was a tendency for both indicators of hygiene to increase. It also showed that S. aureus had the capacity to develop in LinguiAga despite the increasingly-adverse conditions of the food matrix. In relation to the second principal component (27%), Enterobacteriaceae counts and Aw had both positive correlations, suggesting that as Aw decreases along processing, the Enterobacteriaceae levels also tend to diminish. In the hi-dimensional projection of the principal components, for both factories, the finished products tend to present lower levels of Enterobacteriaceae and higher levels of S. aureus.